Effectiveness of Elastomeric Bearings in Reducing Pounding Effects between Reinforced Concrete Buildings under Seismic Condition - M. Riski Audri Rahman; Ashar Saputra; Iman Satyarno (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study investigates seismic pounding hazards between adjacent reinforced concrete buildings in East Java, particularly those designed under older regulations without pounding considerations. Nonlinear time history analysis was performed on three building models using eleven pairs of earthquake records scaled to SNI 8899:2020, representing Megathrust, Benioff, and Shallow Crustal earthquakes, with only three pairs analyzed in this study. Model 1 allowed free movement, Model 2 included concrete impact links with a 50 mm gap, and Model 3 utilized elastomer bearing links with a 9 mm gap. Results showed that elastomeric bearings reduced pounding forces by 81% to 95%, decreasing link force from 57437 kN to 5745 kN while withstanding axial loads up to 6276 kN, preventing collisions and maintaining structural stability. Additionally, Model 3 exhibited reduced floor accelerations and structural damage compared to Model 2, emphasizing the importance of elastomeric bearings in mitigating seismic pounding risks.